1983
DOI: 10.1083/jcb.96.2.455
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Semliki Forest virus spike glycoprotein rosettes and vesicles with cultured cells.

Abstract: Semliki Forest virus (SFV)-derived spike glycoprotein rosettes (soluble octameric complexes), virosomes (lipid vesicles with viral spike glycoproteins), and liposomes (proteinfree lipid vesicles) have been used to investigate the interaction of subviral particles with BHK-21 cells. Cell surface binding, internalization, degradation, and low pH-dependent membrane fusion were quantitatively determined. Electron microscopy was used to visualize the interactions.Virosomes and rosettes, but not liposomes, bound to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Thus, although purified virus particles contain cholesterol in the virus membrane, they still require cholesterol in the target membrane in order to fuse . Conversely, SFV spike proteins reconstituted into phospholipid liposomes without sterol can still fuse with cholesterol-containing membranes (Marsh et al, 1983). Our studies have shown that irreversible conformational changes occur in both the E1 and E2 subunits of the SFV spike protein upon exposure to low pH Kielian and Heleuius, 1985).…”
Section: Discussionmentioning
confidence: 63%
“…Thus, although purified virus particles contain cholesterol in the virus membrane, they still require cholesterol in the target membrane in order to fuse . Conversely, SFV spike proteins reconstituted into phospholipid liposomes without sterol can still fuse with cholesterol-containing membranes (Marsh et al, 1983). Our studies have shown that irreversible conformational changes occur in both the E1 and E2 subunits of the SFV spike protein upon exposure to low pH Kielian and Heleuius, 1985).…”
Section: Discussionmentioning
confidence: 63%
“…Isolated E glycoproteins form octameric micelles which, however, do not have hemolytic activity (Vaananen and Kaariainen, 1979). The glycoproteins reconstituted into liposomes showed low pH-induced hemolytic and fusion activities (Marsh et al, 1983a). The fusion efficiency was lower (25%) than that of the parent virus, possibly due to lower spike density on the reconstituted membranes.…”
Section: Semliki Forest Virusmentioning
confidence: 95%
“…SFV spike glycoprotein rosettes and reconstituted lipid vesicles (virosomes) have binding properties on BHK cells similar to those of the intact virus. The particles bind preferentially to the microvilli, the binding is pH-dependent and the particles compete for binding sites with intact viruses (Fries & Helenius, 1979;Marsh et al, 1983a). The efficiency with which the particles bind to cells is, however, reduced when compared with intact SFV.…”
Section: Binding To the Cell Surfacementioning
confidence: 99%